Hubungan antara psychological capital dan career adaptability anggota Dit Samapta Polda - Wulandari, Devany Angie; Hasanati, Nida (Cognicia, 2024)
Every individual will go through an exploration stage in their career where individuals still consider their talents, interests and educational background for their careers. There are career obstacles faced by individuals at the beginning of their careers, encouraging them to have career adaptability skills. This research is a correlational quantitative study that aims to determine the relationship between psychological capital and career adaptability at the beginning of the career of members of Dit Samapta Polda. Subjects in this study were 203 members, aged 19-23 years. This study used two measuring instruments, Psychological Capital Questionnaire Scale (PCQ) and the Career Adapt-Ability Scale (CAAS). Based on the correlation analysis using Rank Spearman, it was found that there was a positive and significant relationship between psychological capital and career adaptability with (ρ = 0,433) and sig. (2-tailed) = (0,000) so that the higher the psychological capital, the higher the career adaptability.